2022
DOI: 10.1007/s00787-021-01935-y
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of mental health in at-risk adolescents before and during the COVID-19 pandemic

Abstract: Although cross-sectional studies have shown that the COVID-19 pandemic has negatively affected the mental health of adolescents, the effect of the pandemic on adolescents with pre-pandemic symptoms is unclear. We, therefore, tested the hypothesis that adolescents had increased emotional and behavioral problems during the lockdowns imposed during the pandemic.This study included three measurements in a prospective cohort of 1022 adolescents who were oversampled based on their high risk of developing psychopatho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 34 publications
(44 reference statements)
1
16
0
1
Order By: Relevance
“…At the same time, some studies have not found a differential impact of the COVID-19 pandemic among some children and youths with disability [10][11][12][13][14]. One longitudinal study did not find significant differences compared to pre-pandemic levels in caregiver distress, caregiver life satisfaction, nor internalising or externalising problems in children with intellectual disability [15].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, some studies have not found a differential impact of the COVID-19 pandemic among some children and youths with disability [10][11][12][13][14]. One longitudinal study did not find significant differences compared to pre-pandemic levels in caregiver distress, caregiver life satisfaction, nor internalising or externalising problems in children with intellectual disability [15].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the results of a study by Hamza et al (2021) revealed that although postsecondary students with pre-existing mental health concerns continued to present mental health concerns during the pandemic, they showed similar or improving mental health during the pandemic compared with the previous (pre-pandemic) year [ 50 ]. Another study conducted in the Netherlands also reported decreases in adolescent mental health symptoms among those who had the highest clinical severity of symptoms pre-pandemic [ 51 ]. Taken together, these results may suggest that more vulnerable adolescents develop resilience in the face of other adversities, such as the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Il y a peu de données longitudinales et, tout comme chez l’adulte, il est intéressant d’étudier les données issues de cohortes déjà suivies avant la pandémie. Les données issues d’une cohorte sur 1 222 adolescents déjà suivis et identifiés « à risque » [7] ont permis une mesure avant la pandémie, au début (avril 2020, premier confinement) et en janvier 2021 (deuxième confinement). De façon similaire à ce qui a pu être observé chez l’adulte [24] , la santé mentale des participants antérieurement les plus fragiles sur le plan émotionnel et comportemental s’est moins dégradée pendant la pandémie.…”
Section: Résultatsunclassified